Automated measurement of size of spinal curve in population-based cohorts: validation of a method based on total body dual energy X-ray absorptiometry scans - Jamaludin, A; Fairbank, J; Harding, I; Kadir, T; Zisserman, A; Clark, EM (Elsevier, 2023)
BACKGROUND: Scoliosis is spinal curvature that may progress to require surgical stabilisation. Risk factors for progression are little understood due to lack of population-based research, since radiographs cannot be performed on entire populations due to high levels of radiation. To help address this, we have previously developed and validated a method for quantification of spinal curvature from total body dual energy X-ray absorptiometry (DXA) scans. The purpose of this study was to automate this quantification of spinal curve size from DXA scans using machine learning techniques.